Materialisme dan Elitisme dalam Lirik Lagu Bento Karya Irwan Fals Sebagai Konruksi Wacana Kritis Van Dijk - Fitria Khoirunnisa; Desma Yuliadi Saputra; Rina Andriani (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2026)
This study aims to examine the construction of critical discourse against elitism and materialism in the lyrics of Iwan Fals' song "Bento" using Teun A. Van Dijk's Critical Discourse Analysis (CDA) approach. The CDA approach considers discourse as a social practice that demonstrates the relationship between ideology and power in society. This research was conducted using a qualitative descriptive method with text analysis of micro, macro, and superstructure. The results show that the lyrics of the song "Bento" demonstrate a critique of elitism by depicting the character "Bento" as a symbol of an arrogant, exclusive, and alienated elite class. On the other hand, the lexical choices that emphasize material possession as a means of legitimizing social status and power are translated as materialism. The song "Bento" functions not only as a work of art but also as a tool for social criticism that encourages discussion about resistance to materialism and elitism in society